1991
DOI: 10.1007/bf00172721
|View full text |Cite
|
Sign up to set email alerts
|

Xanthan production in a plunging jet reactor

Abstract: A plunging jet reactor (0.04-0.08 m 3) was used for the production of the exopolysaccharide xanthan with X a n t h o m o n a s campestris. The microorganism was not affected by the p u m p shear force. Similar specific growth rates and xanthan space-time yields to those in other reactor types were achieved at much lower specific power input. The better oxygen sorption efficiency in the jet reactor overcompensated for the effect of p o o r mixing in the wall region at high xanthan concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Interestingly, higher OD600 values, growth rates, minimum DO saturations and equal GFP fluorescence intensities were obtained in the ELR in relation to the STR. This is in agreement with studies of the early loop reactors from the 1980's and 90's which reported that the circulation pump and the ejector in ejector-type loop reactors did not affect microbial growth [13,21,22]. However, the release of GFP into the growth media was higher in the ELR compared to STR, thus indicating higher cell perforation due to shear stress.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, higher OD600 values, growth rates, minimum DO saturations and equal GFP fluorescence intensities were obtained in the ELR in relation to the STR. This is in agreement with studies of the early loop reactors from the 1980's and 90's which reported that the circulation pump and the ejector in ejector-type loop reactors did not affect microbial growth [13,21,22]. However, the release of GFP into the growth media was higher in the ELR compared to STR, thus indicating higher cell perforation due to shear stress.…”
Section: Discussionsupporting
confidence: 90%
“…For this type of reaction, an alternative to the STR concept, in which mixing and dispersing is achieved by a liquid jet generated by an ejector, is widely used and applied in industry. It has been shown that these so called Venturi or ejector loop reactors (ELR) favour higher mass transfer rates compared to the STR at comparable power inputs . Loop reactors with liquid jets in downflow mode especially feature favourable mass transfer characteristics .…”
Section: Introductionmentioning
confidence: 99%
“…Another important aspect that cannot be overlooked is whether a disposables-based approach may affect the overall yield of the process. The unit operations that may be affected by a switch to disposables operation are the fermentation, where a stirred tank has to be replaced by a plunging jet (Zaidi et al, 1991) or an airlift reactor, and the chromatography step, where the column may be replaced by a column prepacked with cheaper media or by multiple batch adsorption/desorption steps. The microfiltration, and periplasmic release steps are not expected to be affected as they remain intrinsically the same as in the conventional process.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Consequently, conventional xanthan gum fermentation has low xanthan concentration (usually below 3% wt/v) and low productivity (usually below 0.5 g/(L·h). There have been many attempts to increase xanthan productivity and to lower energy costs by using new agitation designs (Funahashi et al, 1987; Galindo and Nienow, 1992, 1993; Herbst et al, 1992; Nakajima et al, 1990; Nienow, 1984; Peters et al, 1992; Tecante and Choplin, 1993) and new types of bioreactors (Herbst et al, 1989; Kawase and Tsujimura, 1994; Kessler et al, 1993; Long et al, 1988; Misra and Barnett, 1987; Pons et al, 1989; Suh et al, 1991; Zaidi et al, 1991). Fermentation with water‐in‐oil emulsion (Ju and Zhao, 1993; Schumpe et al, 1991) and cell immobilization using porous Celite beads (Robinson and Wang, 1988), which reduces broth viscosity and improves aeration and oxygen transfer, have also been studied.…”
Section: Introductionmentioning
confidence: 99%